Resposta do cafeeiro à inoculação de fungos micorrízicos arbusculares, em latossolo vermelho, do cerrado - Freitas Konrad, Maria Luiza de; Furlani, Pedro Roberto; Rodrigues Cassiolato, Ana Maria [UNESP]; Dias da Silveira, Adriana Parada (Univ Federal Uberlandia, 2014)
The aim of this study was evaluate the response of two coffee cultivars (tolerant and sensitive to aluminum - Al), inoculated or not by two arbuscular mycorriza fungi (AMF), Gigaspora margarita and Glomus etunicatum, in cerrado Oxisol, with different base saturation. This experiment was conducted under greenhouse conditions, with a complete randomized design, in a 2x3x2 factorial scheme, consisting of 2 cultivars (tolerante and sensitive to Al), 3 treatments with mycorrhizal (inoculated with two species of AMF and without inoculation) and 3 levels of soil base saturation (30, 45 and 53 V%), with five replicates per treatment. The variables were: plant height, stem diameter, leaf area, shoot dry weight, root fresh weight, nitrate reductase activity, chlorophyll concentration, root colonization and number of AMF spores. Mycorrhizae isolates promoted greater response of coffee plants, in acid soil with high concentration of Al, but this response was observed for both cultivars when plants were colonized by G. margarita. The cultivars evaluated showed no differences in Al tolerance when non inoculated.

O objetivo deste trabalho foi verificar a resposta de dois cultivares de café (sensível e tolerante ao alumínio - Al), à inoculação de Gigaspora margarita e Glomus etunicatum, em Latossolo Vermelho do cerrado, com diferentes saturações por bases (30, 45 e 53 %). O experimento foi realizado em casa de vegetação, com delineamento inteiramente casualizado e em esquema fatorial 2x3x3, consistindo de 2 cultivares de (tolerante e sensível a Al), 3 tratamentos com micorriza (com inoculação de duas espécies de FMA e sem inoculação) e 3 níveis de saturação por bases do solo (V%), com cinco repetições por tratamento. As variáveis foram: altura da planta, diâmetro do caule, área foliar, massa da matéria seca da parte aérea, massa da matéria fresca de raiz, atividade da redutase do nitrato, teor de clorofila, colonização micorrízica e número de esporos. Os isolados de micorrizas proporcionaram maior crescimento do cafeeiro em solo ácido com alta concentração de Al, porém esta resposta foi verificada para ambos os cultivares quando colonizados por G. margarita. Os cultivares avaliados não mostraram diferenças quanto à tolerância ao Al quando não micorrizados.
Response of coffee plants colonized inoculation with arbuscular mucorrhizal fungi, in red latosol of Cerrado
Keywords: Arbuscular mycorrhiza; Nitrate reductase; Toxic aluminium; Base soil saturation values; Aluminium tolerance, Coffea arabica